A diagnostic dilemma: a case report - Comer, David M (BioMed Central, 2009)
BACKGROUND: A seventy nine year old lady presented with acute bilateral foot drop and paraesthesia of her lower limbs as a presenting feature of Wegener's Granulomatosis (WG). CASE PRESENTATION: There was no evidence of pulmonary involvement and her renal function was normal. WG can masquerade as very diverse pathology. It is recognised that neuropathy can occur early and often in the absence of more classical pulmonary and renal findings, often resulting in a delay in diagnosis. CONCLUSION: Anti-neutrophil cytoplasmic antibody (ANCA) testing was particularly useful in this case permitting early diagnosis.